Assessment of Spoilage Bacterial Communities in Food Wrap and Modified Atmospheres-Packed Minced Pork Meat Samples by 16S rDNA Metagenetic Analysis - Cauchie, Emilie; Delhalle, Laurent; Taminiau, Bernard; Tahiri, Assia; Korsak, Nicolas; Burteau, Sophie; Fall, Papa Abdoulaye; Farnir, Frédéric; Baré, Ghislain; Daube, Georges (Frontiers in Microbiology, 2020)
Although several studies have focused on the dynamics of bacterial food community, little is known about the variability of batch production and microbial changes that occur during storage. The aim of the study was to characterize the microbial spoilage community of minced pork meat samples, among different food production and storage, using both 16S rRNA gene sequencing and classical microbiology. Three batches of samples were obtained from four local Belgian facilities (A, B, C, D) and stored until shelf life under food wrap (FW) and modified atmosphere packaging (MAP, CO2 30%/O2 70%), at constant and dynamic temperature. Analysis of 288 samples were performed by 16S rRNA gene sequencing in combination with counts of psychrotrophic and lactic acid bacteria at 22°C. At the first day of storage, different psychrotrophic counts were observed between the four food companies (Kruskal-Wallist test, p-value<0.05). Results shown that lowest microbial counts were observed at the first day for industries D and A (4.20.4 and 5.60.1 log CFU/g, respectively), whereas industries B and C showed the highest results (7.50.4 and 7.20.4 log CFU/g). At the end of the shelf life, psychrotrophic counts for all food companies was over 7.0 log CFU/g. With metagenetics, 48 OTUs were assigned. At the first day, the genus Photobacterium (86.7% and 19.9% for food industries A and C, respectively) and Pseudomonas (38.7% and 25.7% for food companies B and D, respectively) were dominant. During the storage, a total of 12 dominant genera (> 5% in relative abundance) were identified in MAP and 7 in FW. Pseudomonas was more present in FW and this genus was potentially replaced by Brochothrix in MAP (two-sided Welch’s t-test, p-value<0.05). Also, a high Bray-Curtis dissimilarity in genus relative abundance was observed between food companies and batches. Although the bacteria consistently dominated the microbiota in our samples are known, results indicated that bacterial diversity needs to be addressed on the level of food companies, batches variation and food storage conditions. Present data illustrate that the combined approach provides complementary results on microbial dynamics in minced pork meat samples, considering batches and packaging variations.